When fringe meets finesse : compact iodine stabilized lasers in two colour length interferometry - Franco, Rubén Enrique Montero (2023)
This master's thesis focuses on developing a feedback loop system for stabilizing semiconductor lasers to low-pressure iodine gas absorption spectra. The goal is to generate stable wavelengths at 531 𝑛𝑚 and 688 𝑛𝑚, essential for precise two-colour length measurement interferometry in laboratories.